REFLEKSI HASIL PENELITIAN EKSPLORATIF DAN TEMATIS ARKEOLOGI ISLAM DI KALIMANTAN - Atmojo, Bambang Sakti Wiku (Balai Arkeologi Kalimantan Selatan, 2006)
The potency of archaeological remains in Kalimantan from the Islamic period in Indonesia is actually great in number; however, researches f?ave been undertaken partially. Not until 2005 that two large-scale-theme researches were carried out concerning mortuary architectureand Islamic city-plan. Researches on mortuary architecture were conducted in South and East Kalimantan, while the Islamic city-plan in Tenggarong and Paser Balengkong. Results from research on mortuary architecture are the identification of tombstone with types of Demak-Troloyo, Bugis and Aceh. On the other hand, the Islamic city-plan research indicates that the old city-plan of Tenggarong and Paser Balengkong conforms with its physiographic conditions either rivers, swamps, lowlands or hills. Archaeological reconnaissance has been carried out in Central and West Kalimantan; however, it is limited on data inventory. This article discusses the results of Islamic investigation in Kalimantan and the prospect of further archaeological researches.